How does Parental Media Mediation Regulate the Association between Digital Parental Awareness and the Parent-Child Relationship? - Bayar, Muammer Enes; Kulaksız, Taibe; TORAN, MEHMET (Springer, 2025)
The parent-child relationship is evolving due to the influence of technology in the digital age. Traditional family dynamics are changing, prompting parents to rethink their approach to children's development and learn how to interact effectively in digital environments. In light of these considerations, this study aims to examine the role of parental media mediation in the relationship between digital parental awareness and the parent-child relationship. The research was conducted as a cross-sectional survey study based on a quantitative research method. The sample consisted of 291 parents with preschool-age children. Data collection tools included the Demographic Information Form, Digital Parental Awareness Scale, Parental Media Mediation Scale, and Child-Parent Relationship Scale. GLM Mediation Model was performed for data analysis. The analysis revealed that parental mediation behaviors partially mediate the parent-child relationship across all dimensions of digital parental awareness, including being a negative role model, digital negligence, efficient usage, and protection from risks.
Keywords: Digital Childhood; Digital Parenting; Early Childhood; Parent-child Relationship; Parental Mediation